2001
DOI: 10.1021/es010814v
|View full text |Cite
|
Sign up to set email alerts
|

On-Road Measurement of Carbonyls in California Light-Duty Vehicle Emissions

Abstract: Emissions of carbonyls by motor vehicles are of concern because these species can be hazardous to human health and highly reactive in the atmosphere. The objective of this research was to measure carbonyl emission factors for California light-duty motor vehicles. Measurements were made at the entrance and exit of a San Francisco Bay area highway tunnel, in the center bore where heavy-duty trucks are not allowed. During summer 1999, approximately 100 carbonyls were identified, including saturated aliphatic alde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
88
1
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(92 citation statements)
references
References 49 publications
2
88
1
1
Order By: Relevance
“…Unlike glyoxal, methylglyoxal had higher EFs for both gasoline and diesel vehicles in the Zhujiang Tunnel than that of 0.03 ± 0.14 and 0.51 ± 0.32 mg km À1 for gasoline and diesel vehicles, respectively, in the Tuscarora Mountain Tunnel . Fuel-based emission factors were obtained in the Caldecott Tunnel (Kean et al, 2001;Ban-Weiss et al, 2008). The mileagebased EFs mentioned above can be converted to fuel-based ones if we have the fuel efficiency and fuel density.…”
Section: Reconstructed Efs For Gvs Dvs and Lpgvsmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike glyoxal, methylglyoxal had higher EFs for both gasoline and diesel vehicles in the Zhujiang Tunnel than that of 0.03 ± 0.14 and 0.51 ± 0.32 mg km À1 for gasoline and diesel vehicles, respectively, in the Tuscarora Mountain Tunnel . Fuel-based emission factors were obtained in the Caldecott Tunnel (Kean et al, 2001;Ban-Weiss et al, 2008). The mileagebased EFs mentioned above can be converted to fuel-based ones if we have the fuel efficiency and fuel density.…”
Section: Reconstructed Efs For Gvs Dvs and Lpgvsmentioning
confidence: 99%
“…Glyoxal and methylglyoxal can both formed from the oxidation of VOCs (Calvert et al, 2000(Calvert et al, , 2002Volkamer et al, 2001) and emitted directly from tailpipes and biomass burning Kean et al, 2001;Hays et al, 2002;Ban-Weiss et al, 2008), yet direct emissions were viewed as being minor when compared to the secondary formation (Volkamer et al, 2005;Fu et al, 2008). As for speciated carbonyls emitted by gasoline and diesel vehicles, data were mostly obtained from tunnel studies carried out in the United States more than a decade ago Kean et al, 2001;Hays et al, 2002), and the trends in carbonyl emissions from vehicles were thereafter reviewed by Ban-Weiss et al (2008). There might exist great uncertainties in estimating global emission of dicarbonyls from vehicles solely based on a few studies in the US, as carbonyl emissions from motor vehicles can be affected by the changing yet varying vehicle types, fuel compositions and emission control technologies worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…These nine carbonyl compounds were chosen since they were the dominant carbonyl species associated with diesel engine emissions (Kean et al, 2001;Kristensson et al, 2004;Legreid et al, 2007). The standard solutions of the nine carbonyl compounds were purchased from Rescek.…”
Section: Discussionmentioning
confidence: 99%
“…Carbonyl compounds are ubiquitous components in atmosphere and play an important role in atmospheric chemistry, which have adverse effects on human health because they are precursors of ozone and peroxyacyl nitrates (Cater et al, 1981(Cater et al, , 1995Hoekman, 1992;Grosjean et al, 1993;Baez et al, 1995;Grosjean et al, 1996). Many studies have found that formaldehyde and acetaldehyde were main species of carbonyl emissions from diesel engines, and their emission factors vary from 2.1 to 38.3 mg/km and 2.4 to 28.0 mg/km, respectively, or 8.0 to 31.0 mg/L Kean et al, 2001;Schmid et al, 2001;Kristensson et al, 2004;Legreid et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…They are the sources of free radicals and organic aerosols, as well as the precursors of organic acids and oxidants, including ozone (O 3 ) and peroxycarboxylic nitric anhydrides (Carlier et al, 1986;Roberts, 1990;Atkinson, 2000). Carbonyls are emitted into the atmosphere from primary anthropogenic (Kean et al, 2001;Kim et al, 2008) and biogenic sources (Seco et al, 2007;Guo et al, 2009), or formed as reaction intermediates from the oxidations of hydrocarbons (Wiedinmyer et al, 2001;Duane et al, 2002;Guo et al, 2013).…”
Section: Introductionmentioning
confidence: 99%